The Deep History of Ourselves: The Four-Billion-Year Story of How We Got Conscious Brains. (19th May 2023) - LeDoux, Joseph
ABSTRACT: The essence of who we are depends on our brains. They enable us to think, to feel joy and sorrow, communicate through speech, reflect on the moments of our lives, and to anticipate, plan for, and worry about our imagined futures. Although some of our abilities are comparatively new, key features of our behavior have deep roots that can be traced to the beginning of life. By following the story of behavior, step-by-step, over its roughly four-billion-year trajectory, we come to understand both how similar we are to all organisms that have ever lived, and how different we are from even our closest animal relatives. We care about our differences because they are ours. But differences do not make us superior; they simply make us different.